Anisotropy in non-Darcy flow in individual rough-walled rock fractures - Yinbin ZHU; Zhen LIAO; Changdong LI; Hongbin LIU; Xihui JIANG (Meitian dizhi yu kantan)
ObjectiveInvestigating the flow behavior of fluids in individual rough-walled rock fractures is fundamental for fully understanding the seepage characteristics of fluids in rock fracture networks. MethodsRock fractures were artificially synthesized based on the fractal theory, and numerical simulations of seepage along these fractures were performed using the COMSOL Multiphysics software. Then, fracture specimens with the same geometric characteristics as numerical models of fractures were prepared using 3D printing technology. In combination with the self-designed equipment for seepage experiments, this study conducted seepage experiments on these fracture specimens under different injection flow rates to investigate the impacts of varying injection directions on the microscopic and macroscopic behavior of non-Darcy flow in 3D individual rough-walled fractures. Results and Conclusions The results indicate that the differences in the surface roughness of rock fractures under different injection directions significantly influenced the seepage characteristics of fractures, with greater flow resistance, flow path tortuosity, and non-Darcy flow effect occurring in the injection direction with higher fracture surface roughness. The developmental degree of eddies in fractures was positively correlated with the fracture surface roughness. Specifically, eddies in the injection direction with higher fracture surface roughness manifested a higher developmental degree compared to those in the direction with lower surface roughness. The Forchheimer equation did not apply to the entire range of Reynolds numbers when describing non-Darcy flow in fractures. Instead, it was sufficiently accurate only in the case of the sufficient occurrence of non-Darcy flow. The higher anisotropy in the surface roughness, non-Darcy flow was more prone to occur along fractures in the direction with higher surface roughness, accompanied by more pronounced differences in flow behavior between both injection directions. Quantitative characterization models for describing the relationships of the critical Reynolds number with the anisotropy factor in the fracture surface roughness and average fracture aperture were established based on the seepage simulations of 3D fractures. The effectiveness of the established models was verified using seepage experiments. The results of this study serve as a reference for more comprehensive research on the anisotropy in non-Darcy flow behavior in rough-walled fractures.